Anthropological theory : An introductory history - McGee, R. Jon 1955- (McGraw-Hill, 2008)
A comprehensive and accessible survey of the history of theory in anthropology, this anthology of classic and contemporary readings contains in-depth commentary in introductions and notes to help guide students through excerpts of seminal anthropological works. The commentary provides the background information needed to understand each article, its central concepts, and its relationship to the social and historical context in which it was written. Six of the 45 articles are new to this edition.